THE EFFECTIVENESS OF PROGRESSIVE MUSCLE RELAXATION TO REDUCE ANXIETY LEVEL IN MENOPAUSE WOMEN: THE EFFECTIVENESS OF PROGRESSIVE MUSCLE RELAXATION TO REDUCE ANXIETY LEVEL IN MENOPAUSE WOMEN - Agus Cetina, Ayu (Physiotherapy and Physical Rehabilitation Journal, 2023)
Background: Humans experience growth and development at various levels of age. With increasing age, growth and development will stop at a stage which results in various changes in body functions. Menopause is the permanent cessation of the menstrual cycle for women who previously had menstruation as a result of the loss of ovarian follicular activity. Objective: To determine the effect of progressive muscle relaxation exercise on anxiety levels in postmenopausal women. Methods: This study uses a pre-experimental method with a pre-post test one group design. Samples were taken as many as 25 respondents with non-probability sampling technique with purposive sampling method, namely sampling based on inclusion and exclusion criteria. Measurements were made using the Hamilton Anxiety Rating Scale (HARS) questionnaire. Results: Based on the Wilcoxon test to determine whether there is an effect of progressive muscle relaxation on reducing anxiety levels in postmenopausal women, the results obtained a significance value of 0.001 (p<0.05). Conclusion: There is an effect of giving progressive muscle relaxation to reduce anxiety levels in postmenopausal women.